Design and fabrication of an automatic flour sieve machine / Muhamad Aris Iskandar Mazlan and Norhisyam Jenal - Mazlan, Muhamad Aris Iskandar; Jenal, Norhisyam (School of Mechanical Engineering, 2023)
In this global era, most people still use a manual flour sieve which is a colander when they are cooking or preparing a mixture for cakes. It takes a very long time to prepare a cake because they cannot multitask while preparing the mixture and more energy is needed in the making of it. Therefore, this project is designed for those who like to cook alone at home because it can save consumers time when cooking and baking cakes. Other than that, it also can reduce human energy consumption. The main mechanical engineering concept used in this project is the dynamic concept which contains rotational and linear motion. The crank and slider mechanism will be used to convert rotational motion to linear motion. When the motor is turned on, the horizontal rotational motion will be transferred to the vertical rotational motion by a bevel gear. Hence, simple wiring is needed to complete the project. Since this project used electrical and mechanical parts that can be harmful to the consumer, the mechanism will be housed within a cover to ensure its safety.